Batak Toba Local Wisdom as a Conceptual Bridge in Primary Mathematics Instruction: A Systematic Literature Review - Taruly Tampubolon; Kaleb E. Simanungkalit (MASI Mandiri Edukasi, 2026)
Indonesian primary education continues to face significant challenges in numeracy, as evidenced by a persistent performance gap between formal mathematical abstractions and students' daily sociocultural contexts. This study explores the potential of Batak Toba local wisdom to serve as a conceptual bridge in elementary mathematics learning. Following the PRISMA protocol, a systematic review was conducted on seven empirical studies retrieved from SINTA-indexed journals published between 2015 and 2025. Inclusion was limited to studies that provided empirical evidence of classroom interventions. Findings reveal that Batak Toba cultural heritage—specifically the geometric symmetries of Ulos textiles, the structural proportions of Rumah Bolon architecture, and the functional designs of Tandok—provides a robust foundation for teaching geometry, measurement, and arithmetic. This integration operates through three primary pathways: the use of artifacts as visual anchors, the alignment of instructional materials with cultural identity, and the implementation of Realistic Mathematics Education (RME) within local settings. The synthesized evidence indicates that these culturally relevant approaches significantly enhance students' conceptual understanding and engagement in learning compared to conventional methods. The study concludes that while indigenous frameworks effectively foster mathematical literacy, further rigorous research is needed to evaluate their efficacy across broader socio-geographical contexts.